Specific Issues of Mandatory Nature and Discretionary Nature of Shareholders Legal Relations’ Regulation (Law and Safety, 2019)
Specific issues of the correlation of mandatory nature and discretionary nature of shareholders legal relations’ regulation have been researched. Based on the analysis of the legislation of Ukraine and other countries, the author has paid attention to the fact that priority should be given to their imperative provision in the framework of shareholders legal relations.The conclusion of a shareholders’ agreement is an example of applying the principle of discretionary nature, when the shareholders of one company independently choose the particular model of behavior for the implementation of their corporate rights. Such rights, in their opinion, are the most effective for corporate interests’ settlement. However, while implementing this principle, it is necessary to observe the limits set by mandatory corporate norms.Shareholders’ agreement under national law is secondary in regard to the charter of a joint-stock company within the limits of mandatory-discretionary regulation of shareholders relations. Such an agreement as a form of manifestation of the discretionary regulation of shareholders relations cannot regulate those social relations that are mandatory regulated by the current legislation. It must comply with the requirements of the legislation, as well as with the by-laws adopted for their itemization.
Keywords: a shareholder; joint-stock company; shareholders’ agreement; legal entity; corporation; freedom of contract; statute